Letters to Judy : what your kids wish they could tell you - Blume, Judy.; Kids Fund (Foundation) (New York : Pocket Bookks, 1986)
The author presents letters from children to her confiding their concerns with friendships, families, illness, sexuality, and other problems; and in return, Ms. Blume shares similar moments from her own life, both as a child and as a parent.
"A Kids Fund project."
Bibliography: p. 274-284.
Keywords: Blume, Judy -- Correspondence; Children -- United States -- Attitudes; Children -- United States -- Correspondence; Parent and child -- United States